The Organizational Excellence and its Role in Achieving Competitive Advantage at Qassim University In View of Saudi Arabia's Vision 2030 - Hailah Al-Towaijri (Deanship of Scientific Research (DSR), the University of Jordan, 2020)
This study aims to find out the role of organizational excellence in achieving competitive advantage in Qassim University as a model for Saudi universities in the light of the vision of Saudi Arabia 2030. To achieve the aim of the study, a descriptive method was used, where the study sample consisted of chairs of academic departments at Qassim University (149) for the first semester of the year 1439 / 1440 AH. The degree of availability of organizational excellence in all its dimensions was medium. Further, the degree of availability of organizational excellence and competitive advantage was medium. Furthermore, the variable of organizational excellence has an impact on predicting the level of competitive advantage at Qassim University from the point of view of the heads of departments, which confirms the possibility of predicting the level of competitive advantage through organizational excellence. This study recommends focusing on the importance of developing the organizational structure at Al-Qassim University, so that it is characterized by flexibility. It also recommends enhancing the participation of all employees of Al-Qassim University in the development of strategic plans at the university.